Religion for Revolution: Shifting Perceptions of Bodily Ritual in the Lebanese Shi‘a Community - Savannah Danielle Dodd (Al-Jami'ah Research Centre, 2014)
This paper applies Cartesian and Weberian theories of rationalization and Leslie Sharp’s concept of bodily commodification to the transition in the observance of Ashura from practices of bodily mortification to blood donation among the Shi‘a community in Lebanon. The author argues that this shift politicizes salvation and sacralises revolution through a process of rationalization, made possible through the invocation of the Karbala Paradigm, in order to facilitate the commodification of blood for political activism. This shift in ritual practice for the commodification of blood has occurred as a result of three key transitions: (i) from body/self-unity to body/self-dualism; (ii) from salvation in the next world to salvation in this world; and (iii) from personal salvation to societal salvation.[Dengan merujuk teori rasionalisasi model Descartes dan Weber serta konsep komodifikasi tubuh dari Leslie Sharp, tulisan ini menelusur pergeseran yang terjadi pada ritual Ashura dari praktik melukai diri menjadi kegiatan donor darah di kalangan Syiah di Lebanon. Proses ini, menurut penulis, telah mengubah konsep penyelamatan dan revolusi sakral melalui proses rasionalisasi. Hal ini terjadi dengan memakai Paradigma Karbala sebagai media komodifikasi darah untuk aktivisme politik. Pergeseran komodifikasi darah dalam praktik ritual ini terjadi melalui tiga transisi utama: (i) dari kesatuan diri menjadi dualisme diri; (ii) dari keselamatan akhirat menjadi keselamatan dunia; dan (iii) dari penyelamatan pribadi menjadi penyelamatan sosial].